A Conceptual Hybrid Approach in Evaluating IT Governance Maturiy Level - Faradillah; Muhammad Fadhiel Alie; Leriza Desitama Anggraini (Politeknik Negeri Madiun, 2021)
This study aims to examine several evaluation standards of IT governance and management, so as to produce a work step that can be used to evaluate both simultaneously. The result of the research is a conceptual joint work step to evaluate IT governance in Higher Education: Studies in Private Universities.In achieving the Tridarma, Private Universities require good knowledge management in IT governance and management governance. As a form of business engaged in education, private universities must also be able to maintain their existence in the business world with increasingly fierce and rapid competition, universities have utilized technology in all aspects, both in the process of providing education and operationally supporting the activities of the tridharma of higher education.The current use of technology is certainly expected to be in line with the goals of higher education. This research proposes work steps that are expected to accommodate the need for evaluation of IT governance and management by combining several clauses contained in COBIT as an evaluation tool for IT governance and ISO 9001:2015 as a standard that focuses on Quality Management System. This study uses interview techniques and direct observation through audits to collect data and evidence using an instrument in the form of a list of questions that have been adjusted to the two standards used, namely COBIT and ISO 9001: 2015.